2018
DOI: 10.1089/scd.2017.0262
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenic Activity of Human Adipose-Derived Mesenchymal Stem Cells Under Simulated Microgravity

Abstract: Multipotent mesenchymal stem/stromal cells (MSCs) are strongly involved in tissue homeostasis mainly through paracrine regulation. In this study, we examined the influence of simulated microgravity on the angiogenic potential of adipose-derived MSCs (ASCs). The conditioned medium (CM) from random positioning machine (RPM)-exposed ASCs stimulated the formation of vessel network in ovo, endothelial cell (EC) capillary-like network, and nondirected EC migration in vitro. These effects were driven by alteration of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 29 publications
0
18
0
1
Order By: Relevance
“…MSCs secrete VEGF, FGF, HGF, placental growth factor (PGF), monocyte chemotactic protein 1 (MCP-1), stromal cell-derived factor 1 (SDF-1), and angiopoietin-1 (Ang-1) that are critical for vascularization [178][179][180][181][182][183]. Several studies have reported the potential of increasing capillaries and newly formed vessels following MSC administration both in vitro and in vivo [184][185][186].…”
Section: Angiogenic Factorsmentioning
confidence: 99%
“…MSCs secrete VEGF, FGF, HGF, placental growth factor (PGF), monocyte chemotactic protein 1 (MCP-1), stromal cell-derived factor 1 (SDF-1), and angiopoietin-1 (Ang-1) that are critical for vascularization [178][179][180][181][182][183]. Several studies have reported the potential of increasing capillaries and newly formed vessels following MSC administration both in vitro and in vivo [184][185][186].…”
Section: Angiogenic Factorsmentioning
confidence: 99%
“…It is expected that the upcoming results contribute to development of new therapeutic concepts for arteriosclerosis. Because of the strong anti-inflammatory and immune regulatory function of MSC, as well as their effect on renewing endothelial function [ 30 , 37 , 38 ], we considered that Ad-MSC administration is safe and may be useful in the treatment and prevention of arteriosclerosis. Additionally, Ad-MSC could serve as an effective adjuvant to the standard statin therapy of arteriosclerosis in order to accelerate improvement.…”
Section: Discussionmentioning
confidence: 99%
“…In experiments with adipose tissue perivascular MSCs (ASCs), we demonstrated decreased expression of a number of adhesion-associated proteins and altered transcriptional activity of genes encoding adhesion proteins and matrix 34 . A modified secretory profile and the resulting increase in the angiogenic potential of ASCs have been shown 35 .…”
Section: Discussionmentioning
confidence: 99%